2013
DOI: 10.1109/tmi.2013.2281620
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Analysis of Laser Speckle Contrast Images Recorded at Rest and During Biological Zero: Comparison With Laser Doppler Flowmetry Data

Abstract: Laser speckle contrast imaging (LSCI) is a newly commercialized imaging modality to monitor microvascular blood flow. Contrary to the well-known laser Doppler flowmetry (LDF), LSCI has the advantage of giving a full-field image of surface blood flow using simple instrumentation. However, laser speckle contrast images are not fully understood yet and their link with LDF signals still has to be studied. To quantify the similarity between LSCI and LDF symbolic sequences, we propose to use, for the first time, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 81 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…This means that, for scale factors larger than three, LDF signals complexity becomes closer to the ones of LSCI time series with the largest ROI size. These results are in accordance with previous works where it has been reported that: (i) there are different dynamical patterns for LSCI and LDF data [26]; (ii) when the ROI size increases in LSCI data and when LSCI pixel values are averaged in ROI and followed with time, the patterns of the resulting time series approach the patterns of LDF signals [26,31,32,38]. Several studies have been carried on compression entropy [34,37,[39][40][41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This means that, for scale factors larger than three, LDF signals complexity becomes closer to the ones of LSCI time series with the largest ROI size. These results are in accordance with previous works where it has been reported that: (i) there are different dynamical patterns for LSCI and LDF data [26]; (ii) when the ROI size increases in LSCI data and when LSCI pixel values are averaged in ROI and followed with time, the patterns of the resulting time series approach the patterns of LDF signals [26,31,32,38]. Several studies have been carried on compression entropy [34,37,[39][40][41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 91%
“…This pixel was followed with time to obtain a time series of 1,600 samples. Moreover, around each pixel chosen above, square regions of interest (ROI) of a size of 3 × 3 pixels 2 (1.44 mm 2 ) and 15 × 15 pixels 2 (36 mm 2 ) were determined [26,31,32]. For each ROI, the mean of the pixel values (in APU LSCI ) inside the ROI was computed and followed on each image of the sequence to obtain a time-evolution signal (see Figure 3).…”
Section: Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological zero has been the subject of many studies using laser Doppler flow and has been suggested as consisting of Brownian motions of molecules as well as local redistribution of blood cells within vessels [22,23]. The interpretation and handling of the biological zero is still under debate, but it has been proposed that the underlying mechanism causing the biological zero may not be probed in the same way by the laser Doppler flow and LSCI techniques [24]. In a similar way, figure 1 illustrates the very same issue where the curves are parallel but with different y-axis intercepts.…”
Section: Discussionmentioning
confidence: 99%
“…There are already experimental studies comparing them [39][40][41][42]. However, not much theoretical comparison has been conducted according to the authors' knowledge.…”
Section: A Comparison Between Ldf and Lscimentioning
confidence: 99%